Relationship between non‐invasive haemodynamic responses and cardiopulmonary exercise testing in patients with coronary artery disease. (13th October 2014) - Sperling, Milena Pelosi Rizk; Caruso, Flávia Cristina Rossi; Mendes, Renata Gonçalves; Dutra, Daniela Bassi; Arakelian, Vivian Maria; Bonjorno, José Carlos; Catai, Aparecida Maria; Arena, Ross; Borghi‐Silva, Audrey
Summary: Background: Non‐invasive assessment of haemodynamic function by impedance cardiography (IC) constitutes an interesting approach to monitor cardiac function in patients with coronary artery disease (CAD). However, such measurements are most often performed at rest, whereas symptoms are also possible during exertion, particularly at higher intensities. In addition, the association between IC during exertion and cardiopulmonary exercise testing (CPX) is not well understood in these patients, which was the aim of this study. Methods: Nineteen men (age = 62 ± 6 years) with CAD [left ventricular ejection fraction (LVEF) = 61 ± 10%] underwent a CPX using an incremental protocol on a cycle ergometer, with simultaneous measurement of IC. Cardiac output (CO), stroke volume (SV), cardiac index (CI), peak oxygen consumption (VO2 ), the oxygen uptake efficiency slope (OUES), circulatory power and ventilatory power were determined. Results: Pearson product‐moment correlation analysis revealed peak VO2 ( r  = 0·46) was significantly related to CO. Peak oxygen pulse (0·52) was associated with SV. OUES was associated with resting SV (0·47) and with peak SV ( r  = 0·52). Conclusion: These findings suggest that IC indices are associated with certain, but not all, established CPX measures in patients with stable CAD.